On Representative Social Capital - Charles Bellemare; Sabine Kröger (Institute for the Study of Labor (IZA), 2004)
This paper analyzes data for a random sample drawn from the Dutch population who reveal their propensity to invest and reward investments in building up social capital by means of an economic experiment. We find substantial heterogeneity in the propensity to invest and in the propensity to reward investments. In particular, we find strong evidence that the young, elderly, and low educated individuals invest relatively less, but are relatively more likely to reward investments in social capital. On the other hand, labor market participation, income, and religion do not have any significant impact on behavior in the experiment.
Keywords: C10; C90; Z13; 330; social capital investments; experimental economics; representative samples; Social Capital; Experiment; Niederlande